2013
DOI: 10.1530/rep-13-0295
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin 1 induces a pro-inflammatory response in murine fetal membranes but does not induce preterm delivery

Abstract: The mechanisms that regulate the induction of term or preterm delivery (PTD) are not fully understood. Infection is known to play a role in the induction of pro-inflammatory cascades in uteroplacental tissues associated with preterm pathological parturition. Similar but not identical cascades are evident in term labour. In the current study, we used a mouse model to evaluate the role of prokineticins in term and preterm parturition. Prokineticins are multi-functioning secreted proteins that signal through G-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
1
4
0
1
Order By: Relevance
“…However, repeated injections of EG-VEGF to gravid mice during late gestation did not trigger any contractions, and mice proceeded normally to term [13]. These findings confirm the notion that EG-VEGF is rather a protecting than a constrictor factor during late pregnancy.…”
Section: Eg-vegf Controls Human Parturitionsupporting
confidence: 76%
See 3 more Smart Citations
“…However, repeated injections of EG-VEGF to gravid mice during late gestation did not trigger any contractions, and mice proceeded normally to term [13]. These findings confirm the notion that EG-VEGF is rather a protecting than a constrictor factor during late pregnancy.…”
Section: Eg-vegf Controls Human Parturitionsupporting
confidence: 76%
“…Figure1 shows that circulating EG-VEGF levels significantly increased toward the end of pregnancy, suggesting a potential role of this factor in the late processes of parturition. The source of EG-VEGF could not be of placental origin because both our group and Lannagan et al [7,13] showed that placental EG-VEGF production does not increase toward the Comparison of EG-VEGF serum levels in nonlaboring pregnant women during the second and third trimester of pregnancy. A total of 25 serum samples were analyzed (second-trimester samples, n ¼ 14; thirdtrimester samples, n ¼ 11).…”
Section: Eg-vegf Circulating Levels Increase During the Third Trimestmentioning
confidence: 71%
See 2 more Smart Citations
“…Ожирение как состояние низкоуровневого воспаления является фактором риска развития ПЭ. Однако не всякое воспаление индуцирует преждевременные роды [2] и не каждое ожирение переходит в ПЭ. Другими словами, существуют определенные условия, позволяющие реализовать ту или иную патологию.…”
unclassified